Hubungan antara Internet Self-Efficacy dengan Prestasi Belajar Siswa Sekolah Menengah Atas (Fokus: Analisis Cluster dengan Metode K-Means dan Louvain) - M Wahid Syaifuddin; Nugroho Arif Sudibyo; Muhammad Irfan (Universitas Cokroaminoto Palopo, 2023)
Internet self-efficacy (ISE) was initiated by Albert Bandura, self-efficacy (SE) is a widely accepted concept that refers to an individual's belief in his ability to complete certain behaviors or tasks in certain situations. The purpose of this study was to determine the relationship between ISE and the learning achievement of 12th-grade high school students. The sample of this study was 12th-grade MIPA 7 SMA Unggulan CT ARSA Foundation Sukoharjo as many as 21 students. ISE data is data obtained from questionnaires distributed to students who have been tested for validity and reliability. On the other hand, learning achievement tests were conducted on students with three-dimensional material. The analysis conducted to determine the relationship between the two variables is bivariate analysis. The results showed that between the ISE variable and Student Learning Achievement, a correlation coefficient value of 0.670 was obtained with a significant relationship between the ISE variable and Student Achievement. The degree of bond correlation value shows a strong/sturdy correlation.